2020
DOI: 10.1186/s13229-020-00340-7
|View full text |Cite
|
Sign up to set email alerts
|

Tsc1 haploinsufficiency in Nkx2.1 cells upregulates hippocampal interneuron mTORC1 activity, impairs pyramidal cell synaptic inhibition, and alters contextual fear discrimination and spatial working memory in mice

Abstract: Background: Mutations in TSC1 or TSC2 genes cause tuberous sclerosis complex (TSC), a disorder associated with epilepsy, autism, and intellectual disability. TSC1 and TSC2 are repressors of the mechanistic target of rapamycin complex 1 (mTORC1), a key regulator of protein synthesis. Dysregulation of mTORC1 in TSC mouse models leads to impairments in excitation-inhibition balance, synaptic plasticity, and hippocampus-dependent learning and memory deficits. However, synaptic inhibition arises from multiple types… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 42 publications
(88 reference statements)
1
23
0
Order By: Relevance
“…5f ). These results are consistent with a recent study showing that pyramidal cell synaptic inhibition is reduced in the hippocampus of adult Nkx2.1-Cre;Tsc1 flox/+ mice 15 . Overall, these results confirm that embryonic deletion of Tsc1 has opposite effects on PV perisomatic synapse formation and maintenance, initially accelerating the formation of PV synaptic innervation and subsequently impairing perisomatic synapses at the maturation phase.…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…5f ). These results are consistent with a recent study showing that pyramidal cell synaptic inhibition is reduced in the hippocampus of adult Nkx2.1-Cre;Tsc1 flox/+ mice 15 . Overall, these results confirm that embryonic deletion of Tsc1 has opposite effects on PV perisomatic synapse formation and maintenance, initially accelerating the formation of PV synaptic innervation and subsequently impairing perisomatic synapses at the maturation phase.…”
Section: Resultssupporting
confidence: 94%
“…Over the past 15 years, numerous studies have provided evidence that alterations in E/I balance may be involved in many mouse models of monogenetic autism, however the nature of the underlying mechanisms are heterogeneous thus highlighting that it is critical to understand what sort of circuit alterations are caused by specific genetic mutations 6 . While numerous studies have focussed on the effects of Tsc1/2 deletion, and mTOR dysregulation, on cortical and hippocampal excitatory cells 7 10 , only few studies have addressed whether and how Tsc1/2 deletion affects cortical GABAergic circuit development 11 15 . In particular, whether it plays different roles in specific GABAergic populations is not known.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, those seizure resemble what is observed in human [ 38 ]. While all three models present with varying degrees of behavioral and cognitive deficits [ 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ], their relationship with the rich variety of manifestations observed in ASD and TANDs symptoms in humans is not necessarily straightforward.…”
Section: Mouse Models and Developmentmentioning
confidence: 99%
“…This was a surprising finding, as TSC and epilepsy are generally associated with increased neuronal activity. Indeed TSC neurons are hyperactive in culture [ 14 ] and mouse studies have shown decreased synaptic inhibition [ 17 ] and reductions in GABA receptor GABA A R causing hyperexcitability [ 16 ]. It is important to note that VGAT is expressed on GABAergic vesicles located at the presynapse.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown hyperactive neuronal networks in TSC mouse models and stem cell-derived human neuron cultures [ 9 , 14 , 15 , 16 ]. These changes in network excitability are often associated with changes in synaptic balance, like a decrease in synaptic inhibition [ 17 ] or a decrease in γ-aminobutyric acid (GABA) receptors [ 9 , 16 ]. It is well known that astrocytes play crucial roles in neurodevelopment and can directly influence synaptic transmission [ 18 ].…”
Section: Introductionmentioning
confidence: 99%